PENINGKATAN PEMAHAMAN KONSEP SISWA MELALUI BOOKLET BONGGOLAN PADA MATERI KLASIFIKASI MAKHLUK HIDUP - Munawaroh, Siti; Wahyuni, Eva Ari; Sidik, Rahmad Fajar; Tamam, Badrud; Mu'aziyah, Siti Eneng Sururiyatul (Natural Science Education Research, 2025)
This study aims to determine the improvement of students' concept understanding after using the Bonggolan booklet. The material used in the booklet is the classification of living things. This study uses Research and Development (RD) type of research with the ADDIE development model. The population in this study is students of SMP Negeri 31 Gresik in the 2024/2025 academic year. The subjects of this study are students of class VII-C totaling 31 students. The research instrument used is a student concept understanding test sheet. Based on the research results, it can be concluded that the improvement of students' concept understanding with an N-Gain score of 0.76 is categorized as high. Thus, the Bonggolan booklet on the classification of living things material can improve students' concept understanding. The conclusion of the study shows that the developed Bonggolan booklet is very valid to be used as a science learning material and can improve students' concept understanding.